(untitled) (PAMPA, 2023)
It seeks to know the conditions of formalization of agricultural wage earners in the emerging labor market of socio-productive transformations, in which the wage earning of most of its workers is one of the characteristics of the process of productive transformations for food production The applied methodology It is through multivariate analysis in the Continuous Household Surveys, during the period 2010 - 2015 - 2019 since they incorporate rural territories and it is the period of greatest growth in agrifood production. The main results indicate growth in labor formality among agricultural wage earners in Uruguay, with differential and constant behaviors. Differentials in the productive sector, at the beginning forestry wage earners and in the last years of the period livestock wage earners but constant in the payment of low wages, wage earners with low formal qualifications, working mostly in small and medium-sized companies and with reduced weekly work hours among those per day.